The Influence of Whatsapp Usage and Teacher Interpersonal Communication on Organizational Communication Quality - Isna Siskawati; Ade Masturi; Nurul Hidayati; Marisa Puspita Sary; Anan Nisoh (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Effective organizational communication is essential for the smooth operation of school activities; however, challenges arise in utilizing digital media and the quality of interpersonal interactions among teachers in supporting school goals. This study aims to examine the influence of WhatsApp use and teachers’ interpersonal communication, both partially and simultaneously, on the quality of organizational communication at Rahmania Islamic School. A quantitative correlational approach was used, involving 38 respondents via saturated sampling. Hypothesis testing employed t-tests and F-tests. The results show that the t-value for WhatsApp Use exceeds the t-table value of 1.687, indicating a significant influence of WhatsApp Use on the Quality of Organizational Communication. Conversely, the t-value for Teachers’ Interpersonal Communication is less than 1.687, indicating no significant effect on organizational communication quality. However, simultaneously, WhatsApp Use and Teachers’ Interpersonal Communication together have a significant influence on the Quality of Organizational Communication, with an F-value exceeding 2.87. Conclusion: WhatsApp and interpersonal communication enhance the school’s ability to manage information and boost teacher motivation, satisfaction, and loyalty.